INFORMATION SOCIETY: the instrumental logic of access to information and knowledge - Vinicius Aleixo Gerbasi (Informação em Pauta, 2017)
The idea of an information society cannot dissociate from the socio-productive structure. In contemporary capitalism, the immaterial is a preponderant factor in the productive model. Due to the informational field becomes essential in the productive-economic, scientific and cultural process. Information and knowledge characterize as intrinsic factors to the productive reconfiguration to capitalism, in which the rationalization and appropriation is shaped: Science and Technology, innovation and appropriation of cooperation and social relations. For this reason, their proper operation and instrumentality are very important for the creation of surplus value. This article presents a brief critical analysis of the term information society and highlights the historicalideological plan from which it elaborated. We introduces the concepts of "Knowledge Economy" and "Information Regime". The methodology used is of bibliographic-exploratory nature. As a conclusion, it reflects on the importance of the dissemination of information and knowledge as a process of democratization. The operationalization of scientific information and control methods that seek to capture information and knowledge, and thus generate surplus value, information technologies and citizenship have put in the horizon possible actions and capacities of transformation, even if impartial and unstable.